Psychosocial and economic impacts of a charge in lightweight plastic carrier bags in Portugal: Keep calm and carry on? - Luís, S.; Roseta-Palma, C.; Matos, M.; Lima, M. L.; Sousa, C. (Resources, Conservation and Recycling, 2020)
Reducing plastic waste has become an urgent global challenge. To help fight this problem, European countries have undertaken the mission to reduce lightweight plastic bag consumption. In 2014, Portugal implemented a charge on lightweight plastic bags, calling for an adjustment from both consumers and firms. The present re- search aims to study the psychosocial and economic impacts of this tax measure, namely in terms of acceptability of the measure, potential attitude and behaviour changes, and impact on plastic bag markets. The psychosocial impacts were studied based on an online survey (N = 198) and on available datasets illustrating societal trends. Survey results showed that participants agreed with the charge and with widening it to all types of plastic bags. They attributed environmental motives to its implementation, developed reuse habits and mentioned a de- creased consumption of disposable plastics. In addition, individuals appear more concerned with the impacts of everyday plastic products in the environment, and more willing to pay higher taxes and prices to protect the environment. The economic impacts were studied using available data on the charge revenue and on the production and sales of plastic bags, among others. We illustrate that the implementation of the charge led to a sharp fall in the use of lightweight bags, generating a decrease in the production and sale of plastic bags overall, while avoiding significant impacts on the relevant economic sectors.